Clinical characteristics, disease activity, functional status, and quality of life results of patients with psoriatic arthritis using biological and conventional synthetic disease-modifying antirheumatic drugs - Ayhan KAMANLI; Yıldıray AYDIN; F. Figen AYHAN; Hatice BODUR; Mustafa ÇALIŞ; Erhan ÇAPKIN; Gül DEVRİMSEL and Kevser GÖK and Sami HİZMETLİ and Meltem ALKAN MELİKOĞLU and; l. (Archives of Rheumatology, 2021)
Objectives: This study aims to compare the clinical characteristics, disease activity, and quality of life (QoL) of patients with psoriatic arthritis (PsA) who use biological and conventional synthetic disease-modifying antirheumatic drugs (DMARDs) in a nationwide cohort throughout Turkey. Patients and methods: A total of 961 patients (346 males, 615 females; mean age 46.9±12.2 years; range, 18 to 81 years) with PsA according to the classification criteria for PsA were included in the study. The patients’ demographic and clinical characteristics, physical examination results, Disease Activity Score 28, Disease Activity Index for Psoriatic Arthritis and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Psoriasis Area and Severity Index, Bath Ankylosing Spondylitis Functional Index, Bath Ankylosing Spondylitis Metrology Index, Hospital Anxiety and Depression Scale, Health Assessment Questionnaire, Psoriatic Arthritis Quality of Life (PsAQoL), and short form-36 scores were all recorded. Results: Of the patients, 23% underwent biological DMARD (bDMARD) monotherapy, 42% underwent conventional synthetic DMARD (csDMARD) monotherapy, 10% underwent a csDMARD combination therapy, and 10% underwent a combination bDMARD and csDMARD treatment. The visual analog scale (VAS pain), patient global assessment, physician global assessment, and BASDAI scores were found to be lower among patients using combination treatment of csDMARD and bDMARD, while the swollen joint count was found to be lower among patients using bDMARD. The PsAQoL score was found to be the lowest among patients not using any medication and the highest among those using bDMARD. Conclusion: In our study, patients with PsA were successfully treated with both csDMARD and bDMARD monotherapy. When the biological treatments used for PsA were compared with csDMARD, it was found that biological treatments had a positive effect on both disease activity and the QoL. Combinations of csDMARDs and bDMARDs were preferred in cases in which the disease activity was still high or increased. Because of the highest efficacy of the combined treatment, we highly suggest increasing the number of patients on combined treatment.